KARAKTERISTIK WANITA PENDERITA KISTA OVARIUM DI RUMAH SAKIT VITA INSANI PEMATANG SIANTAR TAHUN 2011-2013 - elicia fadhilah; Hiswani .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACT Ovarian cyst is one of the gynecological benign tumor most often found in women in their reproductive life. Based on Indonesia Demographic Health Survey incidence of ovarian cysts in Indonesia reached 37.2%, and most often found in women aged between 20-50 years and rarely at puberty. To defind the characteristics of women with ovarian cysts patient who are Hospitalized at Vita Insani Hospital in 2011-2013 was a descriptive study with case series design. Population and sample of data 124 patients (total sampling). Data of patient were analyzed by chi-square test, Fisher's Exact and ANOVA. The Research Found Proportion of patients with ovarian cysts: age 28-35 years (32%), Batak (60.5%), Islam (48.4%), high school education (71%), occupation Housewife (50%) , married status (90.3%), lower abdominal pain (56.2%), menstrual irregularities (70.2%), the size of the cyst diameter 2-9 cm (47.6%), benign ovarian cysts (82.3%), surgical treatment (91.9%), the average treatment length 4.5 days or 5 days, the cost of their own (76.6%). There were a significant difference between the proportion of cysts by age (p = 0.000), chi-square test can not be carried out to determine the proportion of the size of the cyst is based on a complaint because there are 5 cells (62.5%) who had epected count <5,there was no significant difference between the proportion of married by medical treatment (p = 0.596). Expected to the hospital in order to improve and maintain the quality of caring the patients with ovarian cysts. And for woman to be more attention to symtoms of ovarian cyst so that disease can be detected quickly.